Composite breakwater of a submerged horizontal flexible porous membrane with a lower rubble mound. (November 2020) - Guo, Y.C.; Mohapatra, S.C.; Guedes Soares, C.
Abstract: An analytical solution of a new composite breakwater consisting of a moored submerged flexible porous membrane and a submerged ruble mound below the membrane is presented. The semi-analytical solution is obtained based on the velocity potential decompositions where the consideration of a dispersion relation with complex wave numbers is not required. The convergence of the series solution is demonstrated by computing the values of the reflection, the transmission, the dissipation coefficients and the vertical force. In addition, the present results are compared against published numerical results and experimental data. In order to analyze the efficiency of the newly developed composite breakwater, the present results are compared with those of a single horizontal submerged moored porous membrane and a single rubble mound breakwater. Furthermore, the effects of design parameters on the performance of the composite breakwater are also analyzed in detail.